Vous êtes sur la page 1sur 3

Time Response Analysis

General expression for the transfer function of IInd order control system is given by
()
2
=
() 2 + 2 + 2
= undamped natural frequency
() = damping ratio
Type of System and it s input

Response

Roots

()
=
() 2 + 2

Case I undamped
=0

1 , 2 =

The roots are purely imaginary

r(t)
2

() = 1 cos

Case II (critically damped)


=1

()
2
2
= 2
=
2
() + 2 + ( + )2

1 , 2 = , The roots are real and equal

r(t)
t
Step input

c(t)

()
2
= 2
() + 2 + 2

Case III over damped

The roots are real and unequal

>1

=
c(t)

r(t)

1 , 2 = 2 1

1.5

=3

t
Step input

Case IV underdamped
<1

t
It taken longer time for the response
to reach steady state
()
2
= 2
() + 2 + 2

1 , 2 = 1 2 =

= 1 2

The roots are complex conjugate


1

r(t)

c(t)
t
Step input

Steady State Error:- If the actual output of a control system during steady state
deviates from the reference input (i.e. desired output), the system is said to possess
a steady state error.
The magnitude of the steady state error in a closed loop control system depends on
its open loop transfer function i.e. ()() of the system.
The error () and input () are related as:
()
1
=
() 1 + ()()
() =

()
1 + ()()

Applying final value theorem,


The steady state error can be determined as
()
0 1 + ()()

= lim () = lim
0

Static error coefficients Kp, Kv and Ka are associated with input as unit step, unit
ramp and unit parabolic, respectively.
Static positional error coefficient Kp is associated with unit step input applied to a
closed loop control system
()
0 1 + ()()

= lim

= lim
0 1 + ()()

1
1 + lim ()()
0

1
1 +

= lim ()()
0

Static Velocity error coefficient Kv. It is associated with unit ramp input applied to
a closed loop control system.

Input = unit ramp


() =

1
2

= lim
0

() 1
1 + ()()

= lim
0

1+()()

1
0 {1+()()}

= lim
= lim
0

1
1
=
()()

= lim ()()
0

Static acceleration error coefficient Ka. It is associated with unit parabolic signal.
Input = unit parabolic

() =
= lim

1
3
()

0 1+()()

0 3 {1+()()}

= lim

= lim

= lim

2
2
0 + ()()

2
2
0 + ()()

= lim 2 ()()
0